An Unwanted Andante over the Sea: The South China Sea Debacle and the Role of Maritime Domain Awareness for Indonesia’s National Security - Abel Josafat Manullang; Yosua Saut Marulitua Gultom; Arfin Sudirman (Indonesian Perspective, 2024)
Being a maritime state, not to mention archipelagic, Indonesia deems the sea as a vital component of its national security. However, Indonesia has witnessed numerous problems facing its maritime security, one of them emanates from a global power like China. Driven by its ambition to claim the South China Sea, China has expanded its claim to encompass parts of Indonesia’s exclusive economic zones near the North Natuna Sea. Such a thing is a brazen step against Indonesia’s territorial integrity and maritime security considering the many confrontations and other violations that have occurred around the vicinity. Against that backdrop, the writers seek to rejuvenate how China’s strides in said area affects Indonesia’s national security along with why maritime domain awareness could be the key in responding to it. In formulating the paper, the writers employ the qualitative research method that entailed the use of both primary and secondary data from the internet. The article also utilizes relevant theoretical concepts to guide the analysis flow, notably maritime security and national security. First, the writers lay out the existing landscape surrounding the issue. Afterwards, an analysis using Buzan’s threat intensity assessment is done which deems the threat from China as a high intensity one. Following that, the primacy of maritime security for Indonesia’s national security and interest is laid out. Finally, a discussion on the potentials of maritime domain awareness is presented. Here, it is argued how Indonesia could further enhance its maritime domain awareness capacity in either domestic or international manner.